Qualitative evaluation of a narrative reflection program to help medical trainees recognize and avoid overuse: "Am I doing what's right for the patient?". Issue 3 (March 2018) - Caverly, Tanner; Matlock, Daniel; Thompson, Jocelyn; Combs, Brandon
Highlights: Medical overuse is a contributor to harm and a barrier to high value care but is hard to recognize. Medical residents were invited to reflect on and write up clinical narratives describing overuse. A qualitative evaluation explored impact of reflective writing on participants. Reflective writing may help trainees recognize and avoid medical overuse. Abstract: Objective: The Do No Harm Project is a novel reflective writing program that encourages medical trainees to reflect on and write up clinical narratives about instances of avoidable medical overuse. Our goal is to describe this program and to explore the effect of the program on those participating. Methods: Semi-structured interviews were conducted to explore how participating in the project influenced the thinking, attitudes, and behaviors of participating internal medicine residents. Interviews were conducted with 20 out of the 24 participants from the first 15 months of the program. Results: The following themes emerged from our analysis: 1) learning through reflection (with three sub-themes: empathy for the patient perspective, a critical approach to one's own clinical practice, and awareness of the problem of overuse); 2) empowerment to discuss instances of overuse and act before it occurs; and 3) perceptions of enhanced evidence-based practice and shared decision-making. Conclusion: Trainees volunteering to complete a reflective writing exercise perceived improved ability to avoid overuse and improved self-efficacy to change clinical behaviors that do not align with optimal patient care. Practice implications: Reflective writing may help trainees recognize and avoid medical overuse.